Biophilic design in heritage indoor workplace in George Town, Penang, Malaysia / Josephine Ong Ming Hui and Azizi Bahauddin - Ong, Ming Hui Josephine; Bahauddin, Azizi (2018)
Current lifestyle influences Malaysian occupants work more than 8 hours a day in order to cope with large workloads and meeting deadline. Majority of the occupants are facing overstressed, negative emotion and lead to unhealthy lifestyle. Several studies show that elements of nature are able to enhance human well-being by reconnecting human with nature elements in built environment, which is known as biophilic design. Therefore, this study aims to create a biophilic design guideline to enhance occupants‟ well-being in heritage adaptive reuse indoor workplace. This study was conducted in Heritage World Site (WHS) in George Town, Penang. Mixed method research design was used to collect data from site. Both qualitative and quantitative data were analysed to validate the overall data and research by cross verifying the information from multiple methods obtained. The results proved that the existing of biophilic design patterns significantly enhance occupants‟ emotional well-being and it can be used as design guideline in the future. This study also investigated the different ways of biophilic design patterns application that can affect the quality of biophilic experiences